Evaluación de un consorcio de bacillus aisladas del manglar de puerto hualtaco para reducir la materia orgánica en sedimentos acuícolas - Romero Requelme, Ariana Jareth; Gualan Salinas, Johanna Margarita (Machala : Universidad Técnica de Machala, 2024)
The intensification of aquaculture production generates sediments accumulation, that represent a serious problem for this sector. For this reason, the objective of this experimental work was to evaluate the effect of a consortium of Bacillus spp. strains isolated from mangroves on the degradation of organic matter accumulated in the sediments of shrimp ponds at low salinity. Bacillus spp. strains were massaged in 2% soy peptone for 72 h to reach a bacterial concentration of 109 cfu/ml. The experimental design was completely randomized (CRD), with three treatments of a mixture of bacteria and the addition of nutrients such as nitrogen and phosphorus (T1 12 µL, T2 18 µL and T3 24 µL) plus a control without application of inputs, each with three replicates. The experiment lasted 20 days, during which the percentage of organic matter (Walkley & Black method), the concentration of total nitrogen (Kjeldahl system), which remained stable throughout the experiment, and the concentration of phosphorus (UV-Visible spectrophotometry), which decreased in T1, were analyzed. The results indicate that there are significant differences in the reduction of organic matter according to the doses of the bacterial consortium, with an average decrease of 3.86%. This study concluded that the use of Bacillus spp. constitutes an effective strategy for the reduction of organic matter in aquaculture sediments at low salinity, contributing to the sustainable management of these systems.
La intensificación de la producción acuícola genera acumulación de sedimento, lo que representan un grave problema para este sector. Por esta razón, el objetivo de este trabajo experimental fue evaluar el efecto de un consorcio de cepas de Bacillus spp. aisladas del manglar en la degradación de materia orgánica, acumulada en los sedimentos de piscinas camaroneras a baja salinidad. Las cepas de Bacillus spp. se cultivaron en peptona de soya al 4 % durante 72 h para alcanzar una concentración bacteriana de 109 ufc/ml. El diseño experimental fue completamente al azar (DCA), con tres tratamientos de una mezcla de bacterias y la adición de nutrientes como nitrógeno y fósforo (T1 12µL, T2 18 µL y T3 24 µL) además de un control sin aplicación de insumos, cada uno con tres repeticiones. El experimento tuvo una duración de 20 días, durante los cuales se analizaron el porcentaje de materia orgánica (método Walkley & Black), la concentración de nitrógeno total (Sistema de Kjeldahl) que se mantuvo estable durante todo el experimento, y la concentración de fósforo (espectrofotometría UV-Visible) que disminuyó en el T1. Los resultados indican que existe diferencias significativas (p-valor < 0,05) en la reducción de materia orgánica, con una disminución promedio del 2.54% en el T3. Este estudio concluyó que el uso de Bacillus spp. constituye una estrategia eficaz para la reducción de materia orgánica en sedimentos acuícolas a baja salinidad, contribuyendo a la gestión sostenible de estos sistemas.
Keywords: BIORREMEDIACION; BACILLUS SPP.; MATERIA ORGANICA; BACTERIAS